Vancomycin, Daptomycin, Antistaphylococcal β-Lactam, and Trimethoprim-Sulfamethoxazole Monotherapy and Combination Therapy in the Management of Methicillin-Resistant Staphylococcus aureus: A Network Meta-Analysis - Xu, Xiaonan; Lu, Ni; Song, Pan; Zhou, Mingzhen; Li, Yuanxiao; Wang, Zirui; Gao, Xin (Frontiers in Pharmacology, 2022)
Objective: The aim was to evaluate the efficacy and safety of vancomycin or daptomycin (VAN/DAP), antistaphylococcal β-lactam (ASBL), trimethoprim-sulfamethoxazole (TMP-SMX) and combination therapy of VAN/DAP+ASBL in the management of Methicillin Resistant Staphylococcus Aureus (MRSA). Methods: Databases including PubMed, Cochrane Library, Embase database, and google scholar were searched on September 1, 2021. The randomized control trials (RCTs) and comparable clinical studies of VAN/DAP, VAN/DAP + ASBL, ASBL and TMP-SMX in the management of MRSA were identified. A network meta-analysis was conducted with STATA 14.0. Results: 7 RCTs and 2 matched cohorts with 1048 patients were included in the analysis. The pooled results showed that VAN/DAP+ASBL had a significantly lower rate of persistent bacteremia >3 days than VAN/DAP alone [OR:0.46, 95%CI (0.26, 0.81), p<0.001]. No obvious differences were observed in the outcomes of all-cause mortality, relapsed bacteremia, microbiological treatment failure, embolic or metastatic infection, total adverse events. However, the ranking results showed that VAN/DAP+ASBL had slightly better efficacy (all-cause mortality, persistent bacteremia >3 days, duration of bacteremia, microbiological treatment failure, and relapsed bacteremia) but slightly higher adverse events than VAN/DAP alone. No obvious differences in the comparisons of VAN/DAP vs ASBL, and VAN/DAP vs TMP-SMX in the analyzed outcomes. The ranking results revealed that ASBL and TMP-SMX didn’t have better efficacy or lower adverse events comparing the treatment of VAN/DAP. Conclusion: The efficacy of VAN/DAP+ASBL was slightly but not significantly better than VAN/DAP alone in the management of MRSA.